2005
DOI: 10.1016/j.acra.2005.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Real-time, Interactive MRI for Cardiovascular Interventions1

Abstract: Over the past decade, there has been a small contingent of laboratories developing magnetic resonance imaging (MRI)-guided intravascular techniques and applications. While these efforts have followed in the footsteps of MRI-guided surgical technologies (1,2), intravascular techniques do not carry the requirement for an open access scanner, and hence higher imaging performance during procedures can be achieved. The concept of precise real-time tracking of an active catheter in a standard MRI scanner was fully r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 71 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…However, for a given number of receiver coils, more undersampling leads to a deteriorating image signal-to-noise ratio and a reduced ability to suppress aliasing artifacts [55]. Balancing these issues, 15 frames-per-second true-FISP cardiac imaging with 128 phase encode lines can be performed using an eight-channel receiver coil array and optimized image reconstruction hardware [56]. Further increases in speed and image quality may be realized with 32-channel and 128-channel receiver coil arrays [57].…”
Section: Real-time Mri Guidance During Catheter Manipulationmentioning
confidence: 98%
“…However, for a given number of receiver coils, more undersampling leads to a deteriorating image signal-to-noise ratio and a reduced ability to suppress aliasing artifacts [55]. Balancing these issues, 15 frames-per-second true-FISP cardiac imaging with 128 phase encode lines can be performed using an eight-channel receiver coil array and optimized image reconstruction hardware [56]. Further increases in speed and image quality may be realized with 32-channel and 128-channel receiver coil arrays [57].…”
Section: Real-time Mri Guidance During Catheter Manipulationmentioning
confidence: 98%
“…McVeigh et al 18 have shown that interventional MRI systems can provide the surgeon with detailed and comprehensive dynamic cardiac images for intra-procedure guidance. However, the use of MRI as an interventional modality has been limited due to the restricted surgical access, incompatibility with most of the standard operating room (OR) equipment, and increased expense and complexity of the procedures.…”
Section: Imaging and Image Guidancementioning
confidence: 99%
“…It offers a 3D-view of the endovascular devices, vascular and cardiac walls [9][10][11][12]. The progress in iCMR is additionally highlighted by the introduction of high-speed parallel MR imaging [13,14] and high-field scanners [15]. Real time imaging comprises the use of efficient pulse sequences like steady state free precession (SSFP; also denoted as balanced TFE, True-FISP, and FIESTA).…”
Section: Mr Imagingmentioning
confidence: 99%
“…Visualization of MR catheters in situ is based on passive and active approaches. Both passive (coating the shaft or tip of the catheter with paramagnetic markers, such as dysprosium oxide, gadolinium oxide, or ferrite admixture) [21,22] and active tracking (incorporating of a receiver coil into the shaft and tip of the catheter) [14,16,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] are currently used in interventional procedures.…”
Section: Mr Devicesmentioning
confidence: 99%